Persepsi tentang Film Kupu-Kupu Malam dan Kajian Pendidikan Agama Kristennya - Putirulan, Meiske; Sopakua, Samel (Didache: Journal of Christian Education, 2024)
“Kupu-kupu Malam” is a beautiful name commonly mentioned by Indonesian citizens for women who work as Commercial Sex Workers. There are various reasons why these women fall into the night world. One of them is faced by Laura, who is played by Michelle Ziudith in the film “Kupu-kupu Malam”. Film is a medium made by humans and is even lifted from the reality of human life. She had to enter the world of prostitution to finance her sister, who was seriously ill because they were orphans and did not have a single family, and the various consequences that she had to face alone for her decision. Starting from having to divide her time to study, working as a “Kupu-kupu Malam”, checking and seeing the development of her sister's health, and accepting the negative stigma and discrimination by society, especially by the man she loves and her family. Talking about night butterfly women among Indonesian people is a sensitive thing, especially if it is done by the closest people because it is an activity that is contrary to the norms of society and the teachings of every religion in Indonesia. The film “Kupu-kupu Malam” premiered on November 25, 2022, and was watched by many young people. They expressed various responses regarding the content and roles played by the film's characters. These responses are what make the author interested in writing it with the study of Christian Religious Education and using a qualitative method approach.